Introduction - Felder, Ekkehard; Jacob, Katharina; Busse, Beatrix; Große, Sybille; Gvozdanović, Jadranka; Lobin, Antje; Lobin, Henning (Handbuch europäische Sprachkritik online, 2025)
There is a connection between the focus of this fifth volume, Language Ideologies and Language Criticism, and those of the first four volumes of the Handbook series. Within a comparison of language cultures, it raises the question of how the much-discussed and discursively established concepts of language standardisation and the standardisation of a national language along with its variants have progressed and how they are currently transforming. These aspects are strongly connected to the first Handbook volume, Critique of Language Norms, as well as to the second, entitled Standardisation and Language Criticism, third, Linguistic Purism and Language Criticism and fourth Handbook volume, Language Institutions and Language Criticism.
Gesehen am 02.02.2026